Penetrasi Budaya Wargee Dalem dan Warga Kilalan dalam Kontruksi Masyarakat Jawa Kuna - Siti Maziyah (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
Java in the 7th century has become one of the trading centers in Southeast Asia. Therefore it is not surprising that in this period of time foreigners have come in various destinations. The inscription calls the foreigners the term wargee dalĕm and wargga kilalan. The purpose of this study was to reveal the foreigners and their relationship with the Old Javanese community. The method used for this study uses a historical method that begins by looking for written sources contained in inscriptions of the 9th century to the 14th century that have been translated and have been published in the form of a collection of inscriptions. The inscription used as data is an inscription that contains terms about wargee dalĕm and wargga kilalan. In addition, Chinese news sources are also used which are related to the problem of trading in Java in the contemporary period. Based on the data, then the origin of the foreign countries was traced, and analyzed for their role in the Old Javanese community. The results of the study show that as one of the central commercial areas in Southeast Asia, it is very possible for Javanese people to connect with foreign nations. The long relationship caused a cultural influence that was caused.